The struggle for language: diagnosis, relief from grief of urban parents with children who are deaf or hard hearing in Ibadan metropolis (2015)
There is little research attention on young children with hard hearing impairment in Ibadan metropolis. A quantitative research method was used to explore and describe the perspectives and practices of these children’s parents’ routines. An ethnographic approach enabled documentation of parent routines, daily activities, thoughts and behaviour (practices). In depth interviews and observations were the primary data sources. Data collection for this study occurred within one year period. Research questions were focused on efforts which caregivers make independently and with others (teachers and family members) to facilitate communication and acquire language development among deaf impaired children. Fifteen parents and eight staff member of Ibadan North local Government Area, Ibadan School for the deaf, Eleyele Road and the deaf unit of Methodist Grammar school disclosed their perspectives and practices. While similarities and differences arose, universal perspectives and practices emerged among parents that are discussed as prevailing themes. Results suggest that caregivers (parents struggle, systemic barriers, and the urban environment are greatest challenges facing family members. Focusing on these challenges will contribute to establishment to just equitable and effective interventions for urban children who are hard of hearing, their caregivers (parents), and other related families